2015
DOI: 10.5455/jice.20141104014605
|View full text |Cite
|
Sign up to set email alerts
|

Anti-conjunctivitis effect of fresh juice of xGraptoveria (Crassulaceae) - a phytochemical and ethnobotanical study

Abstract: Aim:The parent of xGraptoveria, Graptopetalum paraguayense, is used in Chinese folk medicine for alleviating hepatic disorders, detumescence and detoxication, lowering of blood pressure, inhibition of cancer cells, exerting diuretic effects, relieving pain and infections. No data are available regarding its anti-conjunctivitis effect. The aim of this preliminary study is to test the anti-conjunctivitis properties of xGraptoveria (Crassulaceae) and to identify its bioactive constituents.Materials and Methods:Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It was found that GP aqueous extracts show anti-inflammatory [14], antioxidant [15] and antineoplastic activities [16]. Preliminary phytochemical studies on the effect of n-butanol extract from fresh watery juice of GP leaves demonstrate anticonjunctivitis activity due to probable synergistic effect between alkylamines, hydroxycarboxylic, aliphatic and aromatic carboxylic acids [17]. Published data [18] suggest that the GP polyphenolic fraction inhibits hepatitis B virus (HBV) replication, gluconeogenesis and lipogenesis and could be used for treatment of chronic HBV patients.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that GP aqueous extracts show anti-inflammatory [14], antioxidant [15] and antineoplastic activities [16]. Preliminary phytochemical studies on the effect of n-butanol extract from fresh watery juice of GP leaves demonstrate anticonjunctivitis activity due to probable synergistic effect between alkylamines, hydroxycarboxylic, aliphatic and aromatic carboxylic acids [17]. Published data [18] suggest that the GP polyphenolic fraction inhibits hepatitis B virus (HBV) replication, gluconeogenesis and lipogenesis and could be used for treatment of chronic HBV patients.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, awareness of medicinal plants was monitored, as well as their potential adverse effects [21] and sources of information about them [22,23]. At the same time, the proportion of studies that seek to validate available or newly documented ethnobotanical information remains low [24].…”
Section: Introductionmentioning
confidence: 99%